PREVALENCIA DE TRASTORNOS MENTALES EN CONSULTA AMBULATORIA DEL CENTRO DE SALUD DE SAN ANTONIO DURANTE EL PERIODO MAYO - JULIO 2022 (La U Investiga, 2022)
Introduction: Mental and physical disorders have been synchronized, one being the cause or consequence of the other in many cases, however, the neglect of mental health has meant that mental illnesses have increased in recent years and therefore physical ones as well. Objectives: To determine the prevalence of mental disorders and their association with a history of physical, emotional and sexual abuse, in the population over 18 years of age who attend the outpatient clinic of the San Antonio Health Center in the period May-July 2022. Methodology: Quantitative, observational, descriptive study. The study population consisted of 230 people who met the selection criteria. The data collection was carried out using the computerized tool "Global Mental Health Assessment Tool - Primary Care Version", the data was coded in SPSS and subjected to statistical tests that are, calculation of prevalence of mental disorders, measurement of frequencies of each disorder mental present and association of variables. Results: It was found that 42% of the population suffered from one or more mental disorders, of which the most prevalent were depression, personality problems and stress. In addition, an association of variables between mental disorder and history of physical and emotional abuse was identified. Conclusions: These results allow us to conclude that the prevalence of mental disorders is high and that there is a relationship between having a history of emotional and physical abuse with having a mental disorder.Keywords: Mental disorder, physical, emotional, sexual abuse, primary health care.